Zinowiewia sebastianii (Celastraceae), a new high-Andean species from the Colombian Eastern Cordillera (2017)
Zinowiewia sebastianii, a new species from high-Andean forests of the Eastern Cordillera at the department of Boyacá (Colombia) is described and illustrated, and its taxonomic affinities are discussed. Individuals of the new species are shrubs to 5 m tall, with interpetiolar, laciniate stipules, leaf blades with 8–11 pairs of lateral veins and entire, plane margin, 2-forked dichasia to 1 × 1 cm, axillary to the distal leaves, calyx, corolla and androecium pentamerous or tetramerous, and two-celled, one-seeded samaras 18–20 × 5–7 mm. Based on the low number of individuals of Z. sebastianii observed within an area of occupancy 10 km2, in severely fragmented forests, the species is proposed as Critically Endangered (CR), as it faces an extremely high risk of extinction in the wild.